EFEKTIVITAS SANKSI PIDANA DENDA PADA TINDAK PIDANA PERPAJAKAN DALAM MEMAKSIMALKAN PENDAPATAN NEGARA DI WILAYAH HUKUM PENGADILAN NEGERI KOTA SEMARANG - joko pramono (MIH Unsoed, 2022)
Taxes are mandatory contributions to the state owed by a person or entity that is coercive under the Law, by not getting rewarded directly and used for state purposes for the greatest prosperity of the people (Article 1 number 1 of the KUP Law). While resistance to the tax collection process is a phenomenon that often occurs both by utilizing legal loopholes (Tax Avoidance) and through tax evasion efforts.The approach method used in this research is the method of sociological juridical approach. The research specifications carried out are descriptive analysis that describes the symptoms in the community environment to a case studied, the approach taken is a qualitative approach that is a research procedure that produces descriptive data, with primary and secondary data sources.The Juncto KUP Law on Job Creation Law does not regulate the forced implementation of criminal fines that cause inconsistencies in the judge's decision in imposing criminal fines making it difficult for prosecutors as executors in optimizing state revenue from the payment of criminal fines. Legal awareness of taxpayers who want to benefit as much as possible from the business they have run and there is still a presumption that tax money is part of the profits obtained by taxpayers, so that there is abuse and non-compliance of taxpayers who are not right in implementing the self assessment system which ultimately leads to criminal acts in the field of taxation. Taxpayers as convicts prefer to undergo a replacement confinement rather than pay a high fine.